The Impact of AI Voice Bots and Chatbots on Personalized Learning for Lecturers and Students in Tertiary Institutions - Musa , Hussaini Ya’u; Kasim, Bappah Kawu (Kashere Journal of Education, 2025)
Artificial intelligence (AI)-driven conversational technologies, particularly voice bots and chatbots, are increasingly transforming teaching and learning processes in tertiary institutions worldwide. These technologies provide new opportunities for personalised learning, adaptive feedback, and instructional efficiency. This paper examines the impact of AI voicebots and chatbots on personalised learning among lecturers and students at tertiary institutions. Anchored in contemporary theories of personalised and adaptive learning, the study synthesises empirical and conceptual literature on the pedagogical roles of conversational AI, its feedback delivery mechanisms, and efficiency gains for teaching and learning. Findings indicate that AI-powered conversational agents enhance learner engagement, support self-paced learning, provide timely and individualised feedback, and reduce lecturers' workloads by automating routine academic interactions. Nonetheless, challenges pertaining to ethical considerations, data privacy, infrastructural constraints, and pedagogical coherence endure, especially in the context of developing nations. The study concludes that, when strategically and ethically integrated, AI voice bots and chatbots hold substantial potential to improve personalized learning and instructional effectiveness in tertiary education